2009
DOI: 10.3329/bmrcb.v35i2.2534
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone profile in beta-thalassemia major children

Abstract: Keywords: Thalassemia, Thyroid hormone; ChildrenOnline: 26 August 2009DOI: 10.3329/bmrcb.v35i2.2534Bangladesh Med Res Counc Bull 2009; 35: 70-71

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…There was no correlation between thyroid dysfunction and gender and age. Similar results have been documented by Gathwala et al [11].…”
Section: Discussionsupporting
confidence: 92%
“…There was no correlation between thyroid dysfunction and gender and age. Similar results have been documented by Gathwala et al [11].…”
Section: Discussionsupporting
confidence: 92%
“…In thyroid dysfunction, raised TSH level was observed in 24% of Thalassemia patients, which was reliable with diagnosis of subclinical hypothyroidism. Likewise, raised TSH level was the most frequent thyroid dysfunction in prior studies of Pirinccioglu et al, 7 Jaruratanasirikul et al, 8 Malik et al, 9 Hashemizadeh et al 10 and Gathwala et al 11 In this study, 2% of patients had lower T4 and higher TSH, reliable with the diagnosis of overt hypothyroidism. Once again, present study is equivalent to the study done by Solanki et al 12 Similarly many workers, such as Malik et al 9 (1.4%), Hashemizadeh et al 10 (1%), a small number of patients were also found overt hypothyroidism.…”
Section: Discussionsupporting
confidence: 66%
“…Thalassemia major is also known as Cooley's anaemia. Severe beta thalassemia is characterized by transfusion dependent anaemia, usually manifest in the first year of life (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) when HbF declines normally. They manifest as gradually increasing pallor, poor feeding, failure to thrive, irritability, fatigability, intermittent infections (Fever and diarrhoea), jaundice and develop hepatosplenomegaly.…”
mentioning
confidence: 99%
“…22,23 In the present study, compensated hypothyroidism (88.9%) was prevalent among the hypothyroid patients which was consistent with the studies done by Sharmin et al, Zervas et al, Farmaki and Agarwal et al [22][23][24][25] Uncompensated hypothyroidism was only 11.1% among the hypothyroid patients in the present study, which was similar to the study done by Gathwala et al as they found 12% uncompensated hypothyroidism. 26 In our study, all hypothyroid cases had ferritin level of ≥2000 ng/ml and a significant association between hypothyroidism and high ferritin level (≥2000 ng/ml) was found (p=0.028). This finding was consistent with the study done by Hantrakool as they suggested elevated serum ferritin level is a predictor of the development of hypothyroidism in thalassemia patients with iron overload and the maximum serum ferritin levels of greater than 3,500 μg/dl are associated with hypothyroidism in their study.…”
Section: Discussionsupporting
confidence: 51%